Concentration of Mineral Components in Oral Fluid in Children with Undifferentiated Connective Tissue Dysplasia Syndrome and Their Influence on Caries Resistance - M.V. Avdusenko; T.L. Bogdanova (Zaslavsky O.Yu., 2016)
Introduction. The teeth caries resistance can be connected with the anatomical constitution of enamel, determining change of its main characteristics (acidoresistance, permeability, microhardness). Mineralization character is one of lots of features determining enamel caries resistance. Magnesium directly impact organic bone matrix mineralization, collagen production, functional condition of bone tissues, vitamin D metabolism as well as hydroxyapatite crystal growth. In the context of physiology up to 53 % of magnesium is concentrated in the bone tissue, dentine and dental enamel. Magnesium takes a significant role in formation of a normal structure of connective tissue. One of causative factors of connective tissue dysplasia formation is a dyscrasia. Aim of study. To determine a concentration of mineral components in oral fluid in children with undifferentiated connective tissue dysplasia syndrome and to reveal its connection with the dental enamel caries resistance rate. Materials and methods. Fifty children aged from 10 to 12 years old were examined. Concentration of calcium and magnesium in oral fluid was determined by means of biochemical studies. The dental enamel caries resistance was determined by enamel resistance test of V.R. Okushko. Statistical data processing was performed by means of Statistica 6.0 and StatPlus 5.9 packages. Children were divided into two groups: I group was a main one (included 30 persons with undifferentiated connective tissue dysplasia syndrome) and II group was a control one (conditionally healthy children, with a high caries resistance, 20 persons). Results. Average results of mineral components were considerably less in the main group than in the control one: Ca concentration was 0.88 and 1.23 μmol/l, respectively, Mg - 0.25 and 0.44 μmol/l, respectively. Average results of enamel resistance test were 5.83 and 4.15 scores in the main and control groups, respectively. Calcium concentration in oral fluid in the main group compared to the control one was 28.5 % reduced, and magnesium level was 43.2 % reduced. The enamel resistance test showed that the results in the main group are 28.8 % lower than in the control one. Conclusion. There is a deficit in calcium and magnesium concentration in the main group and children of this group need a correction of these microelements level. Insufficient quantity of calcium and magnesium in child's organism leads to enamel dysmorphology. This affects the dental enamel resistance.